(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
The physicochemical properties of polyacrylonitriles, synthesised in the presence of the nitrates of aluminium and copper with the use of spectral methods (IR, UV, NMR), element analysis and X-ray photography have been investigated. It was shown that these polymers are more amorphous and more isotactic than the polymers prepared by the radical mechanisms.